INTERNAL FACTOR AND EXTERNAL FACTOR TO PREDICT FINANCIAL DISTRESS - Ivan Sanjaya; Henryanto Wijaya (Graduate Program of Universitas Tarumanagara, 2024)
The objective of this study is to examine how internal and external factors, such as leverage, liquidity, sales growth, and company size as internal variables, along with inflation and gross domestic product as external variables, impact the financial distress of property and real estate firms listed on the Indonesian Stock Exchange between 2020 and 2022. The sample, comprising 38 companies and 114 data points, was chosen through purposive sampling from secondary sources. Multiple linear regression tests were conducted using Eviews version 12 and Microsoft Excel. The findings indicate that internal factors only partially influence financial distress, and external factors have no significant impact on it. This underscores the necessity for companies to prioritize high-quality management practices to enhance their financial performance and ensure optimal business continuity.